2011
DOI: 10.4103/0971-5916.90992
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the adhesion of putative indigenous probiotic lactobacilli to human colonic epithelial cells

Abstract: Background & objectives:Adherence of bacteria to epithelial cells and mucosal surfaces is a key criterion for selection of probiotic. We assessed the adhesion property of selected indigenous probiotic Lactobacillus strains based on their hydrophobicity and ability to adhere to human epithelial cells.Methods:Five human faecal Lactobacillus isolates, one from buffalo milk and one from cheese were assessed for hydrophobicity following the microbial adhesion to hydrocarbons (MATH) method and colonization potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
48
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(61 citation statements)
references
References 20 publications
(29 reference statements)
11
48
0
2
Order By: Relevance
“…The results indicated that most microorganisms studied were relatively hydrophilic (Table 1). The hydrophilic nature of lactobacilli has often been encountered in previous studies [15, 18, 19]. Three strains, L. plantarum B-578 (52.0 ± 6.4%), L. brevis 20054 (63.1 ± 5.6%), and L. buchneri 20057 (66.9 ± 6.3%), were hydrophobic.…”
Section: Discussionmentioning
confidence: 73%
“…The results indicated that most microorganisms studied were relatively hydrophilic (Table 1). The hydrophilic nature of lactobacilli has often been encountered in previous studies [15, 18, 19]. Three strains, L. plantarum B-578 (52.0 ± 6.4%), L. brevis 20054 (63.1 ± 5.6%), and L. buchneri 20057 (66.9 ± 6.3%), were hydrophobic.…”
Section: Discussionmentioning
confidence: 73%
“…Colonization with extended transit time is most critical for optimal expression of general and specific physiological functions of probiotic microorganisms. Probiotic strains invariably should demonstrate the ability to adhere to the surface mucosal epithelial cells, an important requirement with reference to effective colonization [24]. Cell adhesion which involve contact between the cell membrane of the bacteria and that of the mucosal epithelium is no doubt a complex process.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, adhesion ability can be considered as a standard biomarker for selecting a potential probiotic (Duary et al, 2011). In the present investigation, we evaluated eight probiotic strains of L. reuteri , previously isolated from breast fed infant feces (Singh et al, 2012), for their potential to adhere Caco-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Following incubation, the Caco-2 monolayers were washed with sterile PBS (pH 7.4), Giemsa-stained and examined microscopically under oil immersion, as described previously by Duary et al (2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation